FROM CONFUSION TO CLARITY: THE ROLE OF ACADEMIC ADVISING IN SUPPORTING STUDENT ENGAGEMENT AND SUCCESS - ANDRUSCHENKO, Liudmyla; TEZİKOVA, Svitlana (ISRES Publishing, 2023)
Enrolling in a university or higher education institution can be a daunting experience for students, who often need more certainty and clarity about their academic journey. They may require assistance selecting appropriate subjects, courses, plans, and programs based on their professional interests and goals and understanding requirements, tests, and course changes. In this context, academic advising emerges as a crucial service provided by American colleges and universities, allowing students to navigate their educational paths and achieve their academic and career objectives. However, it remains to be seen whether this model can be implemented successfully in non-American universities, particularly those operating under the Bologna Process. This chapter explores the potential for academic advising to become an integral part of higher education institutions in Ukraine, as a possible example, with a particular focus on foreign language teaching study programmes. By examining the benefits of academic advising in promoting student engagement, monitoring academic progress, and fostering personal and professional growth, we argue that academic advisers could play a vital role in providing educational support to students in non-American universities. In doing so, we seek to answer pertinent questions about the feasibility and desirability of academic advising in non American universities and provide a compelling case for its adoption.
Keywords: academic advisor; student support; higher education; Ukraine